Determination of the Impact of Extruded Soybean Press Cake on Rearing and Health Indices of Piglets - Małgorzata Świątkiewicz; Kinga Szczepanik; Łukasz Gala; Eugeniusz R. Grela; Kamil Witaszek; Marcin Barszcz; Anna Tuśnio; Marcin Taciak (Agriculture)
The study was conducted to evaluate the alternative to imported soybean meal—extruded soybean press cake—in feeding weaning pigs. The experiment was carried out with 20 35-day-old weaned pigs weighing about 8.8 kg, divided into 2 groups (10 pigs in each) differing in the main protein source: group I—control, solvent-extraction soybean meal, group II— extruded soybean press cake. The feed mixtures were iso-protein and iso-energetic. After 35 days of feeding, the pigs were slaughtered. The samples of blood, intestinal tissue and digesta, meat, and back fat were collected for analyses. Replacement of soybean meal with extruded soybean press cake in the weaners’ diet had no statistically significant effect on growth performance and feed utilization. Histomorphometry analysis of the intestines did not indicate any harmful changes. The soybean press cake did not affect the sum of volatile fatty acids in the large intestine, but the ammonia concentration was lower in the distal colon (p ≤ 0.05). It was found that the extruded soybean press cake in the feed significantly affected the fatty acid profile (p ≤ 0.05) of meat and back fat, increasing the amount of PUFAs; however, no negative impact on the durability of meat and back fat during storage was noted. In conclusion, the study confirmed the possibility of completely replacing solvent-extraction soybean meal with extruded soybean press cake in the feeding of weaned pigs.